A Leadership Characteristic Model Of Upright School Administrators Under The Office Of Basic Education Commission - Senamart, Ratchataphorn; Dee-lon, Sittichai; Poldech, Sripen (Journal of Buddhist Education and Research (JBER), 2017)
The purposes of this research were to1) study the leadership characteristics of upright school administrators, 2) construct the leadership characteristic model of upright school administrators 3) evaluate the suitability and possibility and benefit of model. The research was comprised of 2 steps: 1) study the leadership characteristics of upright school administrator 2) construct the leadership characteristic model of school administrators. The sample were the school administrators, teachers and stakeholders by using sampling purpose in the lower Northeast. The statistics used for data analysis were arithmetic mean and standard deviation. The major of research find that 1) the leadership characteristics of upright school under the Office of Basic Education Commission consisted 3 characteristics: conducting oneself conducting people and conducting career 7 aspects; personality, morality, students, teachers and staff, parent and community, academic, and management; 2) The leadership characteristic model of upright school administrators was comprised of 4 parts: Part1) acknowledgement and cognition; Part2) learn and develop comprised of 6 steps: 3.1) evaluation before developing, 3.2) objective 3.3) contents 3.4 activities 3.5 evaluation after developing, and 3.6) redeveloping; Part 3) Guidance the contents to apply, Part 4) conditions of using model.